Mnemonic prediction errors bias hippocampal states - Oded Bein (Nature Portfolio, 2020)
When our expectations are violated, it is adaptive to update our internal models to improve predictions in the future. Here, the authors show that during mnemonic violations, hippocampal networks are biased towards an encoding state and away from a retrieval state to potentially update these predictions.